Characterization of Pseudomonas aeruginosa phage KPP21 belonging to family Podoviridae genus N4‐like viruses isolated in Japan. (January 2016) - Shigehisa, Ryu; Uchiyama, Jumpei; Kato, Shin‐ichiro; Takemura‐Uchiyama, Iyo; Yamaguchi, Kotoe; Miyata, Reina; Ujihara, Takako; Sakaguchi, Yoshihiko; Okamoto, Noriaki; Shimakura, Hidekatsu; Daibata, Masanori; Sakaguchi, Masahiro; et al.
ABSTRACT: Bacteriophages (phages) belonging to the family Podoviridae genus N4‐like viruses have been used as therapeutic agent in phage therapy against Pseudomonas aeruginosa infections. P. aeruginosa phage KPP21 was isolated in Japan, and phylogenetically investigated the phages belonging to this viral genus. Morphological and genetic analyses confirmed that phage KPP21 belongs to the family Podoviridae genus N4‐like viruses. Moreover, phylogenetic analyses based on putative DNA polymerase and major virion protein showed that P. aeruginosa phages belonging to the genus N4‐like viruses are separated into two lineages and that phage KPP21 is in the same clade as phage LUZ7.